Age-Differential Effects of Job Characteristics on Job Attraction: A Policy-Capturing Study - Zacher, Hannes; Dirkers, Bodil T.; Korek, Sabine; Hughes, Brenda (Frontiers in Psychology, 2017)
Based on an integration of job design and lifespan developmental theories, Truxillo, Cadiz, Rineer, Zaniboni, and Fraccaroli (2012) proposed that job characteristics interact with employee age in predicting important work outcomes. Using an experimental policy-capturing design, we investigated age-differential effects of four core job characteristics (i.e., job autonomy, task variety, task significance, and feedback from the job) on job attraction (i.e., individuals’ rating of job attractiveness). Eighty-two employees between 19 and 65 years (Mage = 41, SD = 14) indicated their job attraction for each of 40 hypothetical job descriptions in which the four job characteristics were systematically manipulated (in total, participants provided 3,280 ratings). Results of multilevel analyses showed that the positive effects of task variety, task significance, and feedback from the job were stronger for younger compared to older employees, whereas we did not find significant age-differential effects of job autonomy on job attraction. These findings are only partially consistent with propositions of Truxillo et al.’s (2012) lifespan perspective on job design.